A cost comparison of electronic and hybrid data collection systems in Ontario during pandemic and seasonal influenza vaccination campaigns - Quan Sherman D; Quach Susan; Heidebrecht Christine L; Kwong Jeffrey C; Foisy Julie; Pereira Jennifer A; Guay Maryse; Sander Beate (BMC, 2011)
Abstract Background During the pandemic (H1N1) 2009 influenza vaccination campaign, health regions in Canada collected client-level immunization data using fully electronic or hybrid systems, with the latter comprising both electronic and paper-based elements. The objective of our evaluation was to compare projected five-year costs associated with implementing these systems in Ontario public health units (PHUs) during pandemic and seasonal influenza vaccination campaigns. Methods Six PHUs provided equipment and staffing costs during the pandemic (H1N1) 2009 influenza vaccination campaign and staffing algorithms for seasonal campaigns. We standardized resources to population sizes 100,000, 500,000 and 1,000,000, assuming equipment lifetime of five years and public health vaccine administration rates of 18% and 2.5% for H1N1 and seasonal campaigns, respectively. Two scenarios were considered: Year 1 pandemic and Year 1 seasonal campaigns, each followed by four regular influenza seasons. Costs were discounted at 5%. Results Assuming a Year 1 pandemic, the five-year costs per capita for the electronic system decrease as PHU population size increases, becoming increasingly less costly than hybrid systems ($4.33 vs. $4.34 [100,000], $4.17 vs. $4.34 [500,000], $4.12 vs. $4.34 [1,000, 000]). The same trend is observed for the scenario reflecting five seasonal campaigns, with the electronic system being less expensive per capita than the hybrid system for all population sizes ($1.93 vs. $1.95 [100,000], $1.91 vs. $1.94 [500,000], $1.87 vs. $1.94 [1,000, 000]). Sensitivity analyses identified factors related to nurse hours as affecting the direction and magnitude of the results. Conclusions Five-year cost projections for electronic systems were comparable or less expensive than for hybrid systems, at all PHU population sizes. An intangible benefit of the electronic system is having data rapidly available for reporting.